Farmers’ multidimensional beliefs in orange-fleshed sweetpotato acceptance among rural households in Uganda - Ndaula, S.; Matsiko, F.; Sseguya, H. (2019)
This study sought to assess the role of multi-dimensional beliefs in acceptance of orange-fleshed sweetpotato (OFSP) as an important food for fighting micronutrient deficiencies among rural households in Uganda. Cross-sectional survey data gathered from 341 randomly selected household heads drawn from two districts were analyzed using one-way ANOVA. Post hoc tests indicate that multi-dimensional beliefs (resilience in the field (MD=0.442, p<.05), dry matter content (MD=0.90, p<.05) and control over timely access to labor (MD=0.45, p<.05) significantly enhanced farmers’ decisions to try OFSP cultivation. From trial to sustained cultivation, actions of peers (MD=1.57, p<.001); and control over timely access to labor, (MD=0.55, p<.05), availability of OFSP vines (MD=0.88, p<.001) and control over access to other OFSP farmers (MD=0.63, p<.001) revealed to be important variables. The results also suggest that multi-dimensional beliefs (actions of peers, (MD=1.17, p<.001), approval of peers (MD=1.00, p<.001), control over access to OFSP vines (MD=0.67, p<.001) and control over access to other OFSP farmers (MD=0.70, p<.01)), are vital in supporting farmers to maintain their decisions to cultivate OFSP. We conclude that farmers’ multi-dimensional beliefs are important in the cultivation of OFSP, and farmers’ advancement along each acceptance stage demands for different sets of beliefs. It is recommended that promotion efforts for OFSP and related crop enterprises pay attention to decision-makers’ beliefs.